A systematic review of how patients value COPD outcomes. Issue 1 (19th July 2018) - Zhang, Yuan; Morgan, Rebecca L.; Alonso-Coello, Pablo; Wiercioch, Wojtek; Bała, Małgorzata M.; Jaeschke, Rafał R.; Styczeń, Krzysztof; Pardo-Hernandez, Hector; Selva, Anna; Ara Begum, Housne; Morgano, Gian Paolo; Waligóra, Marcin; et al.
Our objective was to summarise systematically all research evidence related to how patients value outcomes in chronic obstructive pulmonary disease (COPD). We conducted a systematic review (systematic review registration number CRD42015015206) by searching PubMed, Embase, PsycInfo and CINAHL, and included reports that assessed the relative importance of outcomes from COPD patients' perspective. Two authors independently determined the eligibility of studies, abstracted the eligible studies and assessed risk of bias. We narratively summarised eligible studies, meta-analysed utilities for individual outcomes and assessed the certainty of evidence using the Grading of Recommendations, Assessment, Development and Evaluations approach. We included 217 quantitative studies. Investigators most commonly used utility measurements of outcomes (n=136), discrete choice exercises (n=13), probability trade-off (n=4) and forced choice techniques (n=46). Patients rated adverse events as important but on average, less so than symptom relief. Exacerbation and hospitalisation due to exacerbation are the outcomes that COPD patients rate as most important. This systematic review provides a comprehensive registry of related studies. Systematic review of the importance placed by patients on COPD outcomes informs the trade-off between benefits and harms http://ow.ly/l5De30kgD9g